Validation of Steady-State Stability Evaluation Exerting with Dimo's Approximation - Goh, H H; Chua, Q S; Gunadin, I C; Ling, C W; Goh, K C (CEAT 2016 : 4th IET Clean Energy and Technology Conference : 14-15 November 2016, Kuala Lumpur, Malaysia, 2016)
Due to the increasing load requisition and the productiveness of the available transmission size. Therefore the present power systems are abundantly loaded as opposed to the olden days. Hence, these situations are leading the power system to be operated proximately towards the steady-state stability limit (SSSL). Thus, the intension of this paper is to contribute to the evaluation on SSSL in IEEE 9-bus test system based on REI-Dimo technique. REI network will be resulted from the REI-Dimo technique and the results manifested that the test system is implemented with the REI-Dimo technique to reduce the network size and to evaluate the SSSL index.